2020
DOI: 10.21203/rs.3.rs-63080/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Palliative Care Needs among Patients with Advanced Illnesses in Bhutan

Abstract: Background: Palliative care improves the quality of lives of patients and families affected by advanced illnesses through the prevention and relief of suffering. While palliative care is well established in developed countries, it is inadequate or non-existent in most developing countries. Palliative care is an emerging concept in Bhutan, a tiny Himalayan Kingdom. A small community palliative care service is available in the national referral hospital with three dedicated inpatient palliative care beds. This s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Despite our small sample size, the study found that family members caring for non-cancer patients for less than one year were more likely to report high support needs than those caring for more than one year. With regard to diagnosis, although all patients in the concurrent study 28 wanted to know their diagnosis, not all family members in this study were willing to disclose, mainly for fear of causing additional distress and hopelessness. Willingness to disclose a diagnosis, particularly of incurable cancer, is known to depend on social context, cultural norms and family traditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite our small sample size, the study found that family members caring for non-cancer patients for less than one year were more likely to report high support needs than those caring for more than one year. With regard to diagnosis, although all patients in the concurrent study 28 wanted to know their diagnosis, not all family members in this study were willing to disclose, mainly for fear of causing additional distress and hopelessness. Willingness to disclose a diagnosis, particularly of incurable cancer, is known to depend on social context, cultural norms and family traditions.…”
Section: Discussionmentioning
confidence: 99%
“…11 Accordingly, for Bhutan, PC needs among patients with advanced illnesses was explored. 28 Concurrently, besides this study, studies on the perspectives of healthcare professionals on the need for PC and how it should be delivered are underway. The findings of these studies are expected to drive policy changes to integrate PC into the Bhutanese healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Article in Press non-malignant diseases. [4] Palliative care is comprehensive and holistic care provided to patients by an interdisciplinary team of physicians, health-care providers, nurses, psychologists and social workers during hospitalisation and even after discharge. [5] Palliative care is aimed to provide physical, psychological, social and spiritual support to patients with chronic diseases and those in the end stages of life as well as their families through the prevention of suffering.…”
Section: Indian Journal Of Palliative Carementioning
confidence: 99%